Westernization of Medieval Education (Socio-Historical Studies on the Islamic Education of the Ottoman Turkish) - Bambang Yuniarto; Heru Chakra Setiawan; Afif Gita Fauzi (Journal Research of Social Science, Economics, and Management, 2022)
The Ottoman Empire experienced a golden age during the reign of Sultan Sulaiman Al-Qanuni (1494-1566 AD), but after his reign weakened due to advances in European science and technology, in the 18th century the Ottoman Turks tried to restore its glory. by Westernization known as the Reorganization of Turkey. While socio-religious at that time experienced a decline, more than that, dynamism, creativity, progressivity and freedom of thought also decreased. This study aims to explore the origins of the westernization movement in the history of the development of Islamic education in terms of socio-political, socio-religious and social education. It is hoped that a precise definition of the ideal Islamic education will be obtained that is in accordance with the times and always provides the latest benefits for modern times. This study uses a socio-historical approach, which seeks to uncover and analyze the transformation process of the Islamic education system from a traditional system to a modern system. As a result, it was found that the cause of the decline of Muslims was the thinking of the Turkish people who were shackled by fatalism.